The influence of a magnetic field on photon beam radiotherapy in a normal human TK6 lymphoblastoid cell line - Yudhistiara, Brian; Zwicker, Felix; Weber, Klaus-Josef; Huber, Peter E.; Rühle, Annika; Brons, Stephan; Häring, Peter; Debus, Jürgen; Hauswald, Henrik (BioMed Central, 2019)
The implementation of magnetic resonance imaging (MRI) guided radiotherapy (RT) continues to increase. Very limited in-vitro data on the interaction of ionizing radiation and magnetic fields (MF) have been published. In these experiments we focused on the radiation response in a MF of the TK6 human lymphoblastoid cells which are known to be highly radiosensitive due to efficient radiation-induced apoptosis.
In: Radiation oncology; 14(1)2019, Artikel-Nummer 11,